Endoscopy in Infants With Gastrointestinal Bleeding Has Limited Diagnostic or Therapeutic Benefit. Issue 4 (18th July 2022) - Bose, Paroma; Jacobs, Annalise S.; Cordova, Jorge Gonzales; Gray, Brian W.; Huff, Katie A.; Molleston, Jean P.
Abstract : Objectives: Pediatric gastroenterologists are often consulted to perform diagnostic and therapeutic endoscopy in infants with gastrointestinal bleeding (GIB). The value of endoscopy and risk of complications in this population are not well characterized. We aimed to describe findings and outcomes of infants with GIB who undergo endoscopy. Methods: Retrospective, single-center, cohort study of hospitalized infants ≤12 months who underwent esophagogastroduodenoscopy (EGD) and/or colonoscopy/flexible sigmoidoscopy (COL) for GIB. Current procedural technology codes, international classification of diseases codes, and quality control logs identified infants. Results: Fifty-six infants were identified from 2008 to 2019 (51.8% female; mean age 161.6 days). Seven endoscopies identified sources of GIB: gastric ulcers, a duodenal ulcer, gastric angiodysplasia, esophageal varices, and an anastomotic ulcer. Three infants underwent therapeutic interventions of banding/sclerotherapy of esophageal varices and triamcinolone injection of an anastomotic ulcer. Six infants underwent abdominal surgery for GIB or suspected intestinal perforation after endoscopy, where a gastric perforation, jejunal perforation at an anastomotic stricture, necrotizing enterocolitis totalis with perforation, Meckel's diverticulum, and a duodenal ulcer were identified. No source of bleeding was identified surgically in 1 infant with GIB. Respiratory failure, use of vasopressors or octreotide, administration of blood products, and high blood urea nitrogen were associated with increased likelihood of requiring surgery ( P < 0.05 for all). Conclusions: There was limited utility to performing endoscopy in infants ≤12 months old with clinical GIB. Endoscopy in these sick infants carries risk, and 3 infants in this series presented with a gastrointestinal (GI) perforation shortly after the procedure. These limitations and risks should influence clinical decision-making regarding endoscopy in infants with GIB.